Distribution and extent of benthic habitats in Puck Bay (Gulf of Gdańsk, southern Baltic Sea) - Adam Sokołowski; Emilia Jankowska; Piotr Balazy; Agnieszka Jędruch (Oceanologia)
The majority of the southern Baltic Sea seabed encompasses homogenous soft-bottom sediments of limited productivity and low biological diversity, but shallow productive areas in the coastal zone such as wetlands, vegetated lagoons and sheltered bays show a high variety of benthic habitat types offering favourable biotopic conditions for benthic fauna. Within Polish marine areas, semi-enclosed Puck Bay (the western part of the Gulf of Gdańsk) features an exceptionally diverse environment covering a range of benthic habitats which underscores its unique biological value and aesthetic quality and providing an impetus for conservation and ecosystem-based development. Full-coverages maps on benthic habitats in this area are therefore a necessary foundation for maritime spatial planning and implementation of strategies for sustainable management and protection of the coastal environment. This study presents the first comprehensive description and distribution of benthic habitats in Puck Bay which were categorised using the revised EUNIS 2019 classification system. Typological analyses were carried out based on inventory datasets from 1995 to 2019 including scientific publications, satellite images, open databases, topographic and geological maps, reports, theses, information available on websites and unpublished data shared willingly by individual researchers and administrative institutions. Collating various spatial data sources, that were first georeferenced and then visualized using techniques available in ArcMap 10.4.1 software (Esri), resulted in the mapping of benthic habitats and sites of important and protected plant species, which can contribute to the high confidence in environmental assessments and monitoring activities.